ANALISIS MOTIVASI KERJA DALAM MENINGKATKAN PRODUKTIVITAS KARYAWAN - Pratama, Angga (JURISMA : Jurnal Riset Bisnis & Manajemen, 2022)
Every employee has high work motivation with the hope that in the future it can increase work productivity. This study aims to analyze work motivation in increasing employee productivity at PT Jaya Sentra Metal, South Tangerang. This study uses a qualitative descriptive analysis approach. Data was collected through interviews, observations and documentation used to obtain data about photos or pictures of life from the object of research in the unit of analysis using SWOT and QSPM analysis techniques. The stages of data analysis were carried out through activities, namely data collection, data reduction, data presentation, and conclusion. The results of the IE matrix analysis can be seen that the company's position is in Quadrant I. The company's employees have two types of motivation, namely positive motivation and negative motivation. The factors that influence employee motivation to decrease work productivity are the lack of rewards and benefits provided by the company. Keywords: Work Motivation, Productivity, Employee, IE Matrix, SWOT